Pollution of “Akmenės cementas” vicinity: alkalizing microelements in soil, composition of vegetation species and projection coverage - Stravinskienė, Vida (Journal of Environmental Engineering and Landscape Management, 2011)
The article presents the results of the research pertaining to forest litter and the composition of peat topsoil microelements, as well as the composition and projection coverage of undergrowth, herbaceous and bryophyte species specific to the vicinity of the cement factory “Akmenes cementas” are presented. Increased amounts of strontium, barium, titanium, manganese, copper, chromium, nickel and boron in forest litter and the upper 10 cm peat layer (up to 6 km from the pollution source) were established. 53 plant species were observed. The greater part (75–81%) of them are vascular plants. It was indicated that the diversity of vegetation species at different distances (0.5–1.0, 3.0–3.5 and 5.5–6.0 km) from the pollution source varies. Species of broadleaved trees and shrubs (Quercus robur L., Betula pendula Roth., Frangula alnus Mill., Corylus avellana L.), resistant to the impact of alkaline dust, are more outspread near the pollution source. Nearby the pollution source (0.5–1.0 km), Campylium stellatum Lange and Campylium sommerfeltii Lange, were found. At the farthest distances from the plant, the typical for Myrtillo-oxalidosa site type moss Hylocomium splendens (Hedw.) Schimp., Rhytidiadelphus triquetrus (Hedw.) Warnst, and herbs Epilobium palustre L., Vaccinium myrtillus L., Moehringia trinervia (L.) Clairv. were observed. Total coverage of vegetation species varied from 35.5±1.9% at the closest to the pollution source distance to 19.6±2.1% at the 3.0–3.5 km distance. It is significantly (p;<;0.05) less in comparison to the control (51.9±2.2%). The greatest part (43–72%) of the coverage in different squares of the vegetation study consisted of herbs and undergrowth plants. Article in English. ”Akmenės cemento“ aplinkos tarša. Dirvožemį šarminantys mikroelementai, augalijos rūšių į vairovė ir projekcinis padengimas Santrauka. Pateikami miško paklotės ir durpinio dirvožemio mikroelementinės sudėties, trako augalų , žolių bei samanų rūšių į vairovės bei projekcinio padengimo ”Akmenės cemento“ aplinkoje tyrimų rezultatai. Nustatyta, kad dėl cemento dulkių nusėdimo miško paklotėje ir durpėse (iki 6 km atstumu nuo gamyklos) yra padidėjęs mikroelementų (stroncio, bario, titano, mangano ir nikelio, chromo, vario, boro) kiekis; dėl cemento dulkių ir pelenų emisijos dirvožemis šarmejo. šis procesas lėmė augalijos rūšių sudėties skirtumus 0,5–1,0, 3,0–3,5 ir 5,5–6,0 kilometrų atstumu nuo gamyklos. Aptiktos 53 augalų rūšys; daugumą (75–81%) jų sudaro induočiai augalai. Arčiausiai (0,5–1,0 km) gamyklos gausiau išplitę šarminėms dulkėms atsparūs Quercus robur L., Betula pendula Roth., Frangula alnus Mill., Corylus avellana L. bei kalcifilinės žolės Campylium stellatum(Hedw.) Lange et C.E.O. Jensen, Campylium sommerfeltii (Myrin) Lange. Toliau nuo gamyklos randamos durpiniam mėlyngiriui būdingos samanos Hylocomium splendens (Hedw.) Schimp. ir Rhytidiadelphus triquetrus (Hedw.) Warnst.; gausėja šiam miško tipui būdingų žolių rūšių : Epilobium palustre L., Vaccinium myrtillus L., Moehringia trinervia (L.) Clairv. Augalų rūšių projekcinis padengimas kinta nuo 35,5±1,9% (arčiausiai gamyklos) iki 19,6±2,2% 3,0–3,5 km atstumu nuo gamyklos, t. y.patikimai (p<0,05) mažiau už kontrolę (51,9±2,2%). Didžią ją dalį (43–72%) augalijos projekcinio padengimo sudaro žoliniai ir trako sumedėję augalai. Reikšminiai žodžiai: tarša cemento dulkėmis, šarminantys mikroelementai, trako, žolių ir samanų rūšių sudėtis bei projekcinis padengimas. Загрязнение окружающей среды завода «Акмянес цементас»: подщелачивающие микроэлементы в почве, видовой состав и проектное покрытие растительности Резюме. Представлены результаты исследования состава микроэлементов в лесной подстилке и верхнем слое торфа, видового состава и проектного покрытия подлеска, трав и мхов в окружающей среде цементного завода «Акмянес цементас». Установлено увеличенное количество микроэлементов (стронция, бария, титана, марганца, свинца, хрома, никеля, бора) в лесной подстилке и верхнем (10 см) слое торфа на расстоянии до 6 км от завода. Обнаружено 53 вида растений, большую часть (75–81 %) которых составляют сосудистые растения. Разнообразие растительных видов на разном (0,5–1,0, 3,0–3,5 и 5,5–6,0 км) расстоянии от источника загрязнения меняется. Устойчивые к воздействию подщелачивающей пыли лиственные подлеска Corylus avellana L., Quercus robur L., Frangula alnus Mill., Betula pendula Roth распространены вблизи источника загрязнения. Там же найдены виды, характерные для более плодородных типов леса: Rubus idaeus L., Rubus caesius L., Cirsium oleraceum (L.) Scop, Poaceae травы. На более удаленном от завода расстоянии (5,5–6,0 км) найдены характерные для леса типа Myrtillo-oxalidosa мхи Hylocomium splendens (Hedw.) Schimp. и Rhytidiadelphus triquetrus(Hedw.) Warnst. Увеличено число видов трав, характерных для этого типа леса: Epilobium palustre L., Vaccinium myrtillus L., Moehringia trinervia (L.) Clairv. Среднее проектное покрытие наземной растительности меняется от 35,5±1,9 % (вблизи завода) до 19,6±2,2 % на расстоянии 3,0–3,5 км от завода. Это достоверно (р < 0,05) ниже контрольных данных. Большую часть (43–72 %) составляет покрытие травянистых растений и подлеска. Ключевые слова: загрязнение цементной пылью, подщелачивающие микроэлементы, видовой состав и проектное покрытие растительности подлеска, трав и мхов.